2022
DOI: 10.1186/s12935-022-02510-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in stem cell marker and osteopontin expression in primary and recurrent glioblastoma

Abstract: Background Despite of a multimodal approach, recurrences can hardly be prevented in glioblastoma. This may be in part due to so called glioma stem cells. However, there is no established marker to identify these stem cells. Methods Paired samples from glioma patients were analyzed by immunohistochemistry for expression of the following stem cell markers: CD133, Musashi, Nanog, Nestin, octamer-binding transcription factor 4 (Oct4), and sex determini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Stem cell factors, such as OCT-4 and NANOG, are critical for pluripotency and the ability to self-renew embryonic cells and are also thought to play a role in GBM development and recurrence [ 36 , 37 ]. A2B5 and GFAP are markers for neuroglial stem cells [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Stem cell factors, such as OCT-4 and NANOG, are critical for pluripotency and the ability to self-renew embryonic cells and are also thought to play a role in GBM development and recurrence [ 36 , 37 ]. A2B5 and GFAP are markers for neuroglial stem cells [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…This glycophosphoprotein modulates multiple mechanisms of tumor-mediated immune suppression and has a pivotal role at the crossroads of in ammation and tumor progression. OPN plays an important role in tumor reparing, processes of remodelling the extracellular matrix after injury and is also responsible for protumorigenic reprogramming of TAM [45]. In experimental studies, OPN de ciency was associated with reduced immune-suppressive activity of M2 macrophages and decreased OPN/CD44 signaling lead to promotion of aggressive tumor growth as a conseqeunce of enhancement of cancer stem cell activity in the glioma perivascular niche [46].…”
Section: Discussionmentioning
confidence: 99%
“…As with the research field focused on resistance, recurrence has become another growing area of interest due to the affiliation of recurrence with CD133+ cells. Across studies, it has been identified that recurrent GBM has higher expressions of CD133 when compared to the initial tumors [ 27 ]. This is significant because it shows that there are more CSCs in the recurrent tumor, possibly due to the contribution of CD133.…”
Section: Cd133 and Recurrencementioning
confidence: 99%
“… Modified Sankey diagram sorting the publications used into publication type, year, and subgroup [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. …”
Section: Figurementioning
confidence: 99%